1999
DOI: 10.1088/0953-8984/11/25/304
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioband structure calculations of Mg3N2and MgSiN2

Abstract: Ab initio band structure calculations were performed for MgSiN 2 and Mg 3 N 2. Calculations show that both nitrides are semiconductors with direct energy gaps at. The valence bands are composed mainly of N 2p states hybridized with s and p characters of the metals. The bottom of the conduction band consists of the s characters of Mg and N for Mg 3 N 2 , as well as for MgSiN 2 , while the characters of Si are higher in energy. The optical diffuse spectra show an energy gap of about 2.8 eV for Mg 3 N 2 and 4.8 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 29 publications
9
55
2
Order By: Relevance
“…The excitation spectrum spans a broad wavelength range, limited on the short wavelength side by the host absorption [13], which appears not to be very efficient. The emission and excitation behaviour is in good correspondence with literature data [10].…”
Section: Methodsmentioning
confidence: 99%
“…The excitation spectrum spans a broad wavelength range, limited on the short wavelength side by the host absorption [13], which appears not to be very efficient. The emission and excitation behaviour is in good correspondence with literature data [10].…”
Section: Methodsmentioning
confidence: 99%
“…Reckeweg et al reported in 2003 that the band gap of Mg 3 N 2 was 2.8 eV (direct) through reflectance measurements [21]. The band gap values of Mg 3 N 2 calculated by different methods were reported to be from 1.10 eV to 2.25 eV [22][23][24]. Jiao Hao et al took the experimental and theoretical studies on structural phase transformations of Mg 3 N 2 at high pressure in 2009, and got that a reversible, first-order structural phase transition from the ambient cubic phase (Ia-3) to a high-pressure monoclinic phase (C2/m) is found to start at about 20.6 GPa and complete at about 32.5 GPa, and further predicted a second phase transition from the monoclinic phase to a hexagonal phase (P-3m1) around 67 GPa [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of David et al, 21 MgSiN 2 ceramic samples were synthesized by Bruls et al [22][23][24] and studied mainly in terms of their thermal properties as possible substrates for integrated circuits as a replacement for AlN. Work on ceramic samples of MgSiN 2 was also reported by Lenčèš et al 25 Several previous computational studies were performed [26][27][28][29][30][31] but most of these studies used density functional theory in the local density approximation which is not reliable for band gaps. The purpose of this study is to start filling this lack of knowledge by calculating their electronic band structure with a reliable predictive approach.…”
mentioning
confidence: 99%